2022
DOI: 10.1039/d2ea00028h
|View full text |Cite
|
Sign up to set email alerts
|

Probing the impact of a phytoplankton bloom on the chemistry of nascent sea spray aerosol using high-resolution mass spectrometry

Abstract: Sea spray aerosol is the largest natural source of aerosol to Earth’s atmosphere with significant impacts on climate. Despite this, estimates of the impact of sea spray aerosol on Earth’s...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 115 publications
0
8
0
Order By: Relevance
“…Together, the lower O/C and higher H/C values in the SML indicate that those molecules may be more hydrophobic. This is consistent with previous studies of DOM in SML and subsurface waters that found the SML DOM to have more formulas containing H/C > 1.25 and O/C in the range of 0.10–0.40. , Also, the consistently lower O/C in the SML samples, compared to the subsurface water samples, suggests that there is no additional photochemical processing in the SML beyond that in the subsurface water …”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…Together, the lower O/C and higher H/C values in the SML indicate that those molecules may be more hydrophobic. This is consistent with previous studies of DOM in SML and subsurface waters that found the SML DOM to have more formulas containing H/C > 1.25 and O/C in the range of 0.10–0.40. , Also, the consistently lower O/C in the SML samples, compared to the subsurface water samples, suggests that there is no additional photochemical processing in the SML beyond that in the subsurface water …”
Section: Discussionmentioning
confidence: 96%
“…Together, this indicates that a large fraction of the identified organic formulas are aliphatic and that these formulas are representative of molecules that are similar in composition, including H/C and O/C, of known surfactants, lipids, and fatty acids. 33,34,38 Previous studies identified aliphatic formulas as those containing H/C greater than 1.0 and a DBE to carbon (DBE/C) ratio of less than 0.3. 39 In this study, average DBE for each sample ranged from 7.36 to 8.41, for both ionization modes, and average DBE/C ranged from 0.31 to 0.47 (median of 0.35).…”
Section: Characteristics Of Organic Compoundsmentioning
confidence: 99%
See 3 more Smart Citations